A comparative study of the efficacy and requirement of remifentanil infusion alone versus remifentanil infusion + midazolam for end stage renal failure (ESRF) patient during tenckhoff insertion in monitored anaesthesia care (MAC) : a randomized controlled double blinded trial - Kim Lip, Yap (2015)
Introduction: Remifentanil ,an ultra-short acting opioid analgesic, may be useful as an intravenous adjuvant to local anaesthetic for treating patient discomfort and pain during monitored anesthesia care ( MAC). However , the remifentanil dose requirement , interaction with other commonly used sedative drug ( such as midazolam ), and the safety profile especially in ESRF patient for tenckhoff surgery have not been determined . Therefore , this study was designed to define the appropriate dose of remifentanil hydrochloride alone or combined with midazolam , and at the same time to evaluate the safety and efficacy of remifentanil during tenckhoff surgery MAC setting . Methods: 58 patients scheduled for tenckhoff catheter insertion under MAC setting were recruited in this double‐blind study after approved by Research and Ethics Committee, school of Medical Sciences, University Sains Malaysia, Kelantan Health Campus. However, 3 patients had drop off due to convert general anaesthesia. Patients were randomly assigned to one of two groups: ( 1) remifentanil TCI starting at 0.5ng/ml plasma concentration + placebo normal saline , ( 2) remifentanil TCI starting at 0.5ng/ml plasma concentration + midazolam 0.02mg/kg . Standard local anesthetic ( LA) ( max dose of 2 mg /kg levobupivacaine ) was allowed to be injected after that. Verbal assessments of pain, discomfort and sedation according to modified OAA/S score were assessed with 1 st LA injection. The level of pain , discomfort and sedation were subsequently assessed every 5 minutes. Patient oxygen saturation, respiratory rate and heart rate were monitored at 5 minutes interval. Remifentanil was titrated (in increments of 0.1ng/ml from the initial rate) to limit patient discomfort or pain intraoperatively and the infusion was terminated at the completion of skin closure. Post operatively, patient were assessed for incidence of opioid’s side effect such as nausea , vomiting and pruritus Results: At the time of the local anaesthetic, more patients in the remifentanil + placebo group experienced severe pain (78.6%) and severe discomfort ( 46.4%) as compared with midazolam + remifetanil group ( 29.6% and 11.1%, respectively). The final mean }SD remifentanil TCI were 1.57 } 0.11 ng/ml (remifentanil + placebo ) and 0.92 } 0.11 ng/ml (remifentanil + midazolam). Midazolam + remifentanil group achieved pain score <4 in the faster time ( minutes) compared with placebo group ( 9.78 vs 22.36 minutes ; p < 0.05 ) Generally, Midazolam + remifentanil group patients had higher incidences of all adverse evenst intraoperatively. 7 patients (25.9%) in the remifentanil + midazolam group and 2 patients (7.1%) in the remifentanil alone group experienced brief periods hypoventilation (< 8 breaths/min). On the other hand, Remifetanil placebo group patient had higher incidence of post operative opioid side effects . 7 patients (25%) in the remifentanil placebo group and 1 patients (3.7%) in the remifentanil + midazolam group experienced vomiting . Conclusions TCI remifentanil provided effective analgesia and comfort during MAC at a mean plasma concentration 1.57ng/ml when administered alone, or at a mean plasma concentration of 0.92ng/ml in combination with midazolam. Thus , the adding of midazolam in combination with TCI remifentanil could reducing the dose of TCI remifentanil used , and faster time to achieve satisfactory pain score during surgery. However, there were increased incidences of intraoperative adverse even ( hypotension , bradycardia and respiratory depression ) with midazolam + remifentanil group and on the other hand, increase incidences of opiods side effecst ( nausea , vomiting , prutitus ) with remifentanil alone . Keyword: Monitored Anesthesia Care , End Stage Renal Failure , Tenkchoff Surgery , Midazolam Remifentanil , Target Controlled Infusion